Measuring economic insecurity: A simulation approach - Matteo Richiardi; Zhechun He (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2020)
We suggest a new individual-based measure of economic insecurity where expectations about the future evolution of individual life courses are derived from a dynamic simulation model. This allows to take into account risks over many dimensions including work, family and health. On the earning side, we summarise the uncertainty over future income trajectories with a monotonically increasing concave function of income, which penalises income volatility over time and over possible individual trajectories while assigning higher value to higher levels of economic resources available. On the expenditure side, we take into account different household characteristics by means of appropriate equivalence scales.
Keywords: 330; Households; Economics; Life Course Analysis; Microsimulation; Income Dynamics